2020
DOI: 10.25248/reac.e5201.2020
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da sintomatologia dolorosa da coluna vertebral em estudantes de graduação em um município do Maranhão

Abstract: O objetivo deste trabalho foi analisar o perfil doloroso na coluna vertebral em estudantes universitários. Trata-se de uma pesquisa de campo analítica, do tipo transversal com abordagem quantitativa de 46 acadêmicos de universidades de um município do Maranhão. Foi aplicado um questionário sócio demográfico e avaliação física (QSDAF), para análise da ocorrência de sintomas dolorosos na região da coluna, decorrente ou não de atividade física. A intensidade da dor foi medida por meio da escala visual analógica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
1
1
2
Order By: Relevance
“…38 In China, on the other hand, young people and health workers were shown to have a high risk of psychological problems in the same context. 39 Most students with CP in the present study (73.3%) reported feeling pain in three or more places, a percentage slightly above a study with undergraduate students from a municipality in Maranhão State (67%) 40 and substantially higher than undergraduate students from Norway (19.1%). 7 Given these findings, we suggest investigating the relationship between these pain sites and their possible causes with the students' daily activities while considering variables such as time dedicated to studying, study location, and ergonomic posture during activities.…”
Section: Discussioncontrasting
confidence: 47%
“…38 In China, on the other hand, young people and health workers were shown to have a high risk of psychological problems in the same context. 39 Most students with CP in the present study (73.3%) reported feeling pain in three or more places, a percentage slightly above a study with undergraduate students from a municipality in Maranhão State (67%) 40 and substantially higher than undergraduate students from Norway (19.1%). 7 Given these findings, we suggest investigating the relationship between these pain sites and their possible causes with the students' daily activities while considering variables such as time dedicated to studying, study location, and ergonomic posture during activities.…”
Section: Discussioncontrasting
confidence: 47%
“…Regarding the practice of physical activity, a study found that 62.28% of the undergraduates do not perform any physical activity or practice some type of physical activity, which may be related to the high prevalence of back pain, and a sedentary lifestyle is considered a risk factor for the onset of spinal pain. 23 The present study brought an unusual but positive finding; 56% of the voluntaries in this study said they engaged in some physical activity. This finding was divergent in the study by Rodrigues 24 where 56 physiotherapy students from the 1st to the 4th year of the course were included, and 69.6% of the volunteers said they did not practice physical activity.…”
Section: Discussionmentioning
confidence: 50%
“…38 Por sua vez, na China, foi mostrado que jovens e trabalhadores da saúde possuem alto risco de problemas psicológicos no mesmo contexto. 39 A maioria dos estudantes com DC do presente estudo (73,3%) relata sentir dor em três ou mais lugares, porcentagem um pouco acima da obtida em estudantes de graduação de um município do Maranhão (67%) 40 e substancialmente mais elevada do que entre os estudantes de graduação da Noruega (19,1%). 7 Sugere-se investigar a relação entre esses locais de dor e suas possíveis causas com as atividades diárias dos estudantes, levando em conta variáveis como tempo dedicado ao estudo, local de estudo e postura ergonômica durante as atividades.…”
Section: Comparaçãounclassified